1983
DOI: 10.1111/j.1476-5381.1983.tb09377.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antiarrhythmic drugs on ventricular fibrillation thresholds of normal and ischaemic myocardium in the anaesthetized rat

Abstract: 1 The effects of agents which produce membrane stabilization (class I), Pl-adrenoceptor blockade (class II), prolongation of the cardiac action potential (class III) or inhibition of the slow inward current (class IV) were investigated for their ability to increase the ventricular fibrillation threshold (VFT) or to modify the fall in VFT consequent upon coronary artery ligation in the anaesthetized rat. 2 The class I agent, Org 6001, increased VFT of normal myocardium and in lower doses reduced the postligatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Electrically-induced arrhythmias Verapamil and quinidine were tested against electrically-induced arrhythmias in conscious and anaesthetized rats by methods similar to those of Martinez & Crampton (1981) and Marshall et al (1983). Stainless steel electrodes were permanently implanted, 0.3 cm apart, into the left ventricle, and their free ends exteriorised in the neck region.…”
Section: Antiarrhythmic Studiesmentioning
confidence: 99%
“…Electrically-induced arrhythmias Verapamil and quinidine were tested against electrically-induced arrhythmias in conscious and anaesthetized rats by methods similar to those of Martinez & Crampton (1981) and Marshall et al (1983). Stainless steel electrodes were permanently implanted, 0.3 cm apart, into the left ventricle, and their free ends exteriorised in the neck region.…”
Section: Antiarrhythmic Studiesmentioning
confidence: 99%
“…Our present results suggest that the suppression of glibenclamide-sensitivie K+ channels may underlie at least partly the mechanism of antiarrhythmic effects of calmodulin-antagonizing antiarrhythmic drugs. In this connection, it is noteworthy that bepridil, a potent calmodulin antagonist, is expected to be clinically effective for ventricular arrhythmia (Marshall et al, 1983;Singh et al, 1985).…”
Section: Effects Of Calmodulin Antagonists On Krn2391-induced K+ Currmentioning
confidence: 99%
“…VFT is widely used for the study of arrhythmia susceptibility and has been shown to predict the increased and decreased susceptibility of the ventricle to arrhythmias in a range of situations [56, 66, 70]. Some investigators are concerned that VFT does not predict the anti-arrhythmic actions of certain drugs and fails to predict the occurrence of spontaneous arrhythmias [71]. However, Harumi et al [72] have demonstrated that anti-arrhythmic drugs can be classified depending upon their effects on VFT, ventricular refractoriness and electrical restitution properties, indicative of the multiple mechanisms of action of many of these drugs.…”
Section: Spontaneous Versus Induced Arrhythmiamentioning
confidence: 99%